Performance assessment of solar air heater duct roughened with perforated-winglet vortex generators - Narin Koolnapadol; Pongjet Promvonge; Sompol Skullong (My University, 2017)
An experimental study has been conducted to investigate heat transfer, friction loss and thermal performance characteristics of turbulent flow in a solar air heater channel artificially roughened on one side (absorber plate) with multiple perforated-winglet vortex generator (PWVG).Air as the working fluid enters the test duct having a uniform surface heat-flux with Reynolds number (Re) ranging from 5200 to 24,000 in the present work.Effects of four different punched hole/pore diameters of winglet (d=2 mm, 4 mm, 6 mm and 8 mm) at a single relative winglet height (R B =b/H=0.6), relative winglet pitch (R P =P/H=3) and attack angle ( = 60°) on thermal characteristics are examined.The experimental results show that the PWVG provides the drastic increase in Nusselt number (Nu) and friction factor (f) values over the flat/smooth channel.In addition, substantial increases in Nu and f values are found for the rise in hole sizes.The maximum Thermal Enhancement Factor (TEF) is found for the pore diameter of 2 mm at lower Reynolds number.The present results are also compared with the results from the typical or solid winglet, TWVG (non-punched hole of winglet).
Keywords: Wingtip device; Vortex generator; Heat Transfer Mechanisms